Identification of targets of monoclonal antibodies that inhibit adhesion and growth in Mycoplasma mycoides subspecies mycoides - Aye, Racheal; Weldearegay, Yenehiwot Berhanu; Lutta, H.O.; Chuma, Francis; Pich, A.; Jores, Joerg; Meens, J.; Naessens, Jan (Elsevier, 2018)
Mycoplasma mycoides subspecies mycoides (Mmm) adhesion is tissue and host specific. Inhibition of adhesion will prevent Mmm from binding to lung cells and hence prevent colonization and disease. The aim of this study was to develop a panel of Mmm monoclonal antibodies against Mmm and use these antibodies to investigate their inhibitory effect on the adherence of Mmm to bovine lung epithelial cells (BoLEC), and to further identify an antigen to any of the inhibitory antibodies. Thirteen anti-Mycoplasma mycoides subsp. mycoides (AMMY) monoclonal antibodies (mAbs) inhibited adhesion by at least 30% and ten of the mAbs bound to multiple bands on Western blots suggesting that the antibodies bound to proteins of variable sizes. AMMY 10, a previously characterized Mmm- capsular polysaccharide (CPS) specific antibody, inhibited growth of Mmm in vitro and also caused agglutination of Mmm total cell lysate. AMMY 5, a 2-oxo acid dehydrogenase acyltransferase (Catalytic domain) (MSC_0267) specific antibody, was identified and polyclonal rabbit serum against recombinant MSC_0267 blocked adhesion of Mmm to BoLEC by 41%. Antigens recognized by these antibodies could be vaccine candidate(s) and should be subsequently tested for their ability to induce a protective immune response in vivo.